Comparison of exhaled and nasal nitric oxide and exhaled carbon monoxide levels in bronchiectatic patients with and without primary ciliary dyskinesia. Issue 1 (1st January 2003) - Horváth, I; Loukides, S; Wodehouse, T; Csiszér, E; Cole, P J; Kharitonov, S A; Barnes, P J
Abstract : Background: Primary ciliary dyskinesia (PCD) is associated with chronic airway inflammation resulting in bronchiectasis. Methods: The levels of exhaled nitric oxide (eNO), carbon monoxide (eCO) and nasal NO (nNO) from bronchiectatic patients with PCD (n=14) were compared with those from patients with non-PCD bronchiectasis without (n=31) and with cystic fibrosis (CF) (n=20) and from normal subjects (n=37) to assess the clinical usefulness of these measurements in discriminating between PCD and other causes of bronchiectasis. Results: Exhaled NO levels were lower in patients with PCD than in patients with non-PCD non-CF bronchiectasis or healthy subjects (median (range) 2.1 (1.3–3.5) ppb v 8.7 (4.5–26.0) ppb, p<0.001; 6.7 (2.6–11.9) ppb, p<0.001, respectively) but not lower than bronchiectatic patients with CF (3.0 (1.5–7.5) ppb, p>0.05). Nasal levels of nNO were significantly lower in PCD patients than in any other subjects (PCD: 54.5 (5.0–269) ppb, non-PCD bronchiectasis without CF: 680 (310–1000) ppb, non-PCD bronchiectasis with CF: 343 (30–997) ppb, control: 663 (322–1343) ppb). In contrast, eCO levels were higher in all patient groups than in control subjects (PCD: 4.5 (3.0–24.0) ppm, p<0.01, other bronchiectasis without CF: 5.0 (3.0–15.0) ppm, p<0.001; CF: 5.3 (2.0–23.0) ppm, p<0.001 v 3.0 (0.5–5.0) ppm). Low values in both eNO and nNO readings (<2.4 ppb and <187 ppb, respectively) identified PCD patients from other bronchiectatic patients with a specificity of 98% and a positive predictive value of 92%. Conclusion: The simultaneous measurement of eNO and nNO is a useful screening tool for PCD.